A strategy to construct alkali-stable anion exchange membranes bearing ammonium groups via flexible spacers1. Issue 29 (7th August 2015) - Yang, Zhengjin; Zhou, Jiahui; Wang, Siwen; Hou, Jianqiu; Wu, Liang; Xu, Tongwen
<x xml:space="preserve">Abstract</x> A novel strategy is provided to construct alkali-stable poly(phenylene oxide) based anion exchange membranes to alleviate cation-induced degradation.